The effect of rearing density on body weight and survival of larval stripped catfish (Pseudoplatystoma sp) into a closed circulating system (Orinoquia, 2016)
In order to evaluate the effects of larval density rearing on body weight and survival of larvae of striped catfish (Pseudoplatystoma sp), was designed and built a closed recirculation system, which allowed maintaining stable physical and chemical variables of water throughout the experimental period. For this purpose, vitelline larvae were rearing in three densities: 10 (T1), 50 (T2) and 100 (T3) larvae per liter and monitored until 20 days post-hatch. They were evaluated four replicates per treatment, kept under photoperiod 0:24 (light: dark) and fed to apparent satiety with Artemia saline hatchlings, which were supplied divided into five portions a day: at 07:00, 09: 00, 14:00, 18:00 and 22:00 hours. The water quality characteristics observed during the test were: dissolved oxygen 5.7 ± 0.5 mg/L; temperature 26 ± 0.8 ° C; pH 7.6 ± 0.2; hardness 38.2 ± 5.2 mgCaCO3/L; alkalinity 26.5 ± 5.2 mg CaCO3 / L; NH3 0.05) were observed. Survival was higher in the density of 10 larvae/L, being statistically different between treatments (86.5 ± 1.9%, 54.7 ± 2.2% and 46.9 ± 3.1% for 10, 50 and 100 larvae/L, respectively, P
Keywords: body weight; density; fish larvae; Pseudoplatystoma sp; survival (Source; AIMS)